Banking on deposit relationships: Implications for hold-up problems in the loan market - Jin Cao; Emilia Garcia-Appendini; Cédric Huylebroek (Norges Bank, 2024)
Theory suggests that by lending to a firm, inside banks gain an informational advantage over non-lender outside banks. This informational gap hinders borrowers from switching lenders due to a winner's curse faced by competing outside banks, leading to hold-up problems. In this paper, we show that firms can reduce this informational gap by forming deposit relationships with outside banks, thereby attenuating hold-up. Using unique data on the deposit and lending relationships of all firm-bank pairs in Norway, we find that having a deposit relationship with non-lender outside banks significantly increases a firm's likelihood of switching lenders. Furthermore, firms that have a prior deposit relationship with new lenders obtain significantly better loan conditions upon switching. In line with informational hold-up theory, these effects are driven by reduced information asymmetries, not cross-selling. Our findings have important implications for open banking and hold-up problems in the loan market.
hdl:11250/3172106
Keywords: G21; D82; L11; L13; 330; Hold-Up problems; Deposit relationships; Lending relationships; Hold-up problems; Lender switching; Information asymmetries